Relationships between Knowledge, Technology Recipient, technology supplier, relationship characteristics and degree of inter-firm technology transfer - Raduan Che Rose; Sazali Abdul Wahab; Jegak Uli; Haslinda Abdullah (2009)
The purpose of this paper is to accentuate on the relationships between knowledge, technology recipient, technology supplier and relationship characteristics and degree of inter-firm technology transfer. A conceptual framework was developed and a review of relevant literature was conducted. Building on the integrated knowledge-based view and organizational learning perspectives, and previous technology transfers models, this study proposes a model in providing explanations on the relationships between technology transfer characteristics and degree of technology transfer. This model also conceptualizes the relationship between the degree of technology transfer and local firms’ performance, specifically at corporate and human resource performance. Building on intra and inter-firm KT literature this paper extends the literature by conceptualizing the relationships between four critical dimensions of TTCHARS (KCHAR, TRCHAR, TSCHAR, and RCHAR) and TTDEG in a single holistic model to explain the relationships between each group of TTCHARS and degree of inter-firm TT in IJVs.